Análisis de las personas del discurso en ensayos escolares* - García Romero, Marisol (Didáctica. Lengua y Literatura, 2004)
The study focuses on an analysis of the use of discursive pronouns in twelve scholarly essays written by university students, with an aim to describing their uses. The essays have been analysed according to enunciation theory (Bajtin, 1982; Beneviste, 1974). The results of the analysis show us that there exists predominant use of the third person as compared to the first or second. We believe that in academic writing students should develop discursive competence in the process of satisfying the textual and discursive demands of such text.
Keywords: Discourse analysis Discourse person Academic writing Essays